2007
DOI: 10.1039/b700699c
|View full text |Cite
|
Sign up to set email alerts
|

How nucleation affects the aggregation of nanoparticles

Abstract: Using the conducting polymer, polyaniline, as a prime example, this article highlights the important role of nucleation on the aggregation of nanoparticles. We demonstrate that during synthesis, irreversible aggregation of nanoparticles can be triggered by heterogeneous nucleation on pre-formed particles. Aggregation can be prevented by mediating the nucleation behavior via experimental conditions including mechanical agitation, reaction temperature and the use of additives. These findings may provide a valuab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 20 publications
1
61
0
Order By: Relevance
“…A variety of theories have been proposed to explain the spontaneous formation of PAni nanofibers under these remarkably simple conditions. [78,[84][85][86][87][88] Some of these suggested theories include, for example, relating the mode of nucleation to the PAni shape, [84,85] the aggregation of aniline dimers [86] and the role of oxidant/oligomer interactions in guiding nanofibers formation. [87] In other words, the theories used to explain this process involve the formation of inherent templates that are incorporated into the polymer chain.…”
Section: Nanofibers Without Templatesmentioning
confidence: 98%
See 1 more Smart Citation
“…A variety of theories have been proposed to explain the spontaneous formation of PAni nanofibers under these remarkably simple conditions. [78,[84][85][86][87][88] Some of these suggested theories include, for example, relating the mode of nucleation to the PAni shape, [84,85] the aggregation of aniline dimers [86] and the role of oxidant/oligomer interactions in guiding nanofibers formation. [87] In other words, the theories used to explain this process involve the formation of inherent templates that are incorporated into the polymer chain.…”
Section: Nanofibers Without Templatesmentioning
confidence: 98%
“…Much of our own work has focused on correlating the shape of PAni with its nucleation mode. [84,85] Because PAni is a water insoluble polymer, its growth is accompanied by a precipitation event. Based on a number of experimental observations, we have suggested that the nucleation mode of PAni can be related to its particle shape: homogeneous nucleation of PAni results in nanofibers while heterogeneous nucleation leads to granular particulates.…”
Section: Nanofibers Without Templatesmentioning
confidence: 99%
“…In contrast to a classical metallic conductor 50 or a polymeric insulator, PAni can be switched reversibly between an insulating emeraldine base form and a conducting emeraldine salt [14] . More recently, interest has developed in the area of nanostructured polyaniline [15][16][17][18][19][20] . These one-dimensional objects 55 combine the advantages of an organic conductor and a high surface area material, thus making them suitable for a diverse range of applications such as chemical sensors, flash memory and electro-optic devices [21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…Forming colloidal dispersions is another method for rendering polymers processable [26]. This method has become especially popular since the advent of nanotechnology in the 1990s.…”
Section: Methods For Inducing Solubilitymentioning
confidence: 99%